Testing the Impact of Batterer Intervention Programs and Court Monitoring in the Bronx (New York City, New York), 2002-2004 - Labriola, Melissa ([Verlag nicht ermittelbar], 2008)
The purpose of this study was to provide a definitive test of whether batterer programs and varying intensities of judicial monitoring reduce reoffending among domestic violence offenders. Study enrollment took place between July 23, 2002, through February 27, 2004. In Part 1, Batterer Program Experiment Data, convicted male domestic violence offenders from court parts AP10 (Pretrial Appearances) or TAP2 (Trials) of the Bronx Misdemeanor Domestic Violence Court were randomly assigned into one of four experimental conditions. The four conditions were batterer program plus monthly judicial monitoring (n = 102), batterer program plus graduated monitoring (n = 100), monthly monitoring only (n = 109), and graduated monitoring only (n = 109). Defendants assigned to a batterer program completed either the Domestic Violence Accountability Program (DVAP) run by Safe Horizon or the Men's Choices Program run by the Fordham Tremont Community Mental Health Center. The offenders were tracked for at least 12 months after sentencing, and for up to 18 months for most of the men, to determine whether they fulfilled the conditions of their sentence, were rearrested for domestic violence, or were reported by the victim to have engaged in new incidents of abuse. Using each offender's New York State criminal identification number, complete criminal record files, including prior criminal history and recidivism, were obtained from the New York State Division of Criminal Justice Services (DCJS). Victims were interviewed about new domestic incidents committed within one year of sentencing. In Part 2, Monitoring Experiment Data, a quasi-experimental study using propensity score matching compared recidivism outcomes between the randomized offenders in Part 1 and a control group of conditional discharge (CD) offenders convicted of identical offenses, but who, as a result of the normal sentencing process, received neither a batterer program nor any form of monitoring. The propensity score predicted the probability of inclusion in the randomized trial (Part 1) sample, based not on actual membership in that sample, but on the statistical probability of membership in it, as computed from the observed set of background characteristics. Each offender in the randomized trial was then matched to the offender in the CD only group with the nearest propensity score. Sometimes multiple offenders from the the initial trial were matched to the same CD only offender. Variables in both Part 1 and Part 2 of the data set include demographic variables for both the defendants and victims, defendant arrest history, current sentence, assignment to a batterer program, type of judicial monitoring, and victim reports of new incidents of violence after sentencing.